2018
DOI: 10.1515/hmbci-2017-0071
|View full text |Cite
|
Sign up to set email alerts
|

Screening for gestational diabetes in low-risk women: effect of maternal age

Abstract: Background Gestational diabetes mellitus (GDM) is on the rise globally and there are various screening guidelines with regard to patients' criteria. Materials and methods We conducted a prospective cross-sectional study to determine the prevalence of GDM amongst low-risk pregnant women above the age of 25 years. A modified glucose tolerance test (MGTT) was performed between 24 and 36 weeks of gestation. Women with GDM were divided into two groups for analysis: age between 25 and 34 years (group A) and above 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…However, the average maternal age for subject with GDM is 30.74 years old. This finding were contradicting with the previous study which reported, women aged 35 years and above are more likely to have GDM (Kalok et al 2018). As expected, systolic and diastolic BP were significantly higher in the PE group compared to the control group (p=<0.0005), and the GDM group (p=<0.0005).…”
Section: Resultscontrasting
confidence: 93%
“…However, the average maternal age for subject with GDM is 30.74 years old. This finding were contradicting with the previous study which reported, women aged 35 years and above are more likely to have GDM (Kalok et al 2018). As expected, systolic and diastolic BP were significantly higher in the PE group compared to the control group (p=<0.0005), and the GDM group (p=<0.0005).…”
Section: Resultscontrasting
confidence: 93%
“…Of the 124 items found from the database and internet search, we included 15 publications in the qualitative analysis (Basri et al 2018;Gill et al 2012;Goh et al 2018;Hasbullah et al 2020;Idris et al 2009;Ismail et al 2013Ismail et al , 2011Kalok et al 2018;Kampan et al 2013;Logakodie et al 2018;Muniswaran et al 2017;Nordin et al 2006;Shamsuddin et al 2001;Tan et al 2012Tan et al , 2007. Two publications with low quality score were excluded (lack of information on the patient recruitment and diagnostic method) (Goh et al 2018;Muniswaran et al 2017).…”
Section: Search Resultsmentioning
confidence: 99%
“…Two publications with low quality score were excluded (lack of information on the patient recruitment and diagnostic method) (Goh et al 2018;Muniswaran et al 2017). Eleven publications provided prevalence data (Basri et al 2018;Gill et al 2012;Hasbullah et al 2020;Idris et al 2009;Ismail et al 2013Ismail et al , 2011Kalok et al 2018;Logakodie et al 2018;Shamsuddin et al 2001;Tan et al 2012Tan et al , 2007. Four publications provided risk factors data (Gill et al 2012;Shamsuddin et al 2001;Tan et al 2012Tan et al , 2007, and seven publications provided maternal, foetal/neonatal complications data (Basri et al 2018;Ismail et al 2013Ismail et al , 2011Kalok et al 2018;Kampan et al 2013;Logakodie et al 2018;Nordin et al 2006).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pregnant women without these risk factors may also develop GDM. Kalok et al [7] conducted a prospective cross-sectional study among low GDM risk pregnant women above the age of 25 years in Malaysia and found the incidence of GDM was 14% in this population. Unfortunately, there is few methods to screen potential GDM in pregnant women with low GDM risk.…”
Section: Introductionmentioning
confidence: 99%